2020
DOI: 10.1371/journal.pone.0238114
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension among people living with human immunodeficiency virus receiving care at referral hospitals of Northwest Ethiopia: A cross-sectional study

Abstract: Introduction Hypertension among HIV positive patients in low-and middle-income countries has got little attention and data on the problem is limited in Ethiopia. Hence, this study aims to determine the magnitude of hypertension and its associated factors among HIV-positive patients receiving care at referral hospitals of Northwest Ethiopia Materials and methods A cross-sectional study design was conducted to determine the burden of hypertension in patients living with HIV receiving care at referral hospitals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 54 publications
2
22
3
Order By: Relevance
“… 27 The above discrepancy might be the difference in inclusion criteria, a study setting, duration of ART, and different sociodemographic characteristics of respondents. In contrast, this study finding is higher than studies done in Harar Jugal Hospital (12.7%), 20 northwest Ethiopia (14%), 28 a study done in Kenya (11.2% and 7.4%) among HIV-positive men and women, respectively, 25 a study done in Parirenyatwa Hospital, Zimbabwe (11.2%), 29 and a study done on HTN prevalence among HIV infected adults in Tanzania (12.5%). 30 The variation might be due to hypertension cutoff point, duration, and regimen of HAART, the difference in socioeconomic and ethnic factors.…”
Section: Discussioncontrasting
confidence: 80%
“… 27 The above discrepancy might be the difference in inclusion criteria, a study setting, duration of ART, and different sociodemographic characteristics of respondents. In contrast, this study finding is higher than studies done in Harar Jugal Hospital (12.7%), 20 northwest Ethiopia (14%), 28 a study done in Kenya (11.2% and 7.4%) among HIV-positive men and women, respectively, 25 a study done in Parirenyatwa Hospital, Zimbabwe (11.2%), 29 and a study done on HTN prevalence among HIV infected adults in Tanzania (12.5%). 30 The variation might be due to hypertension cutoff point, duration, and regimen of HAART, the difference in socioeconomic and ethnic factors.…”
Section: Discussioncontrasting
confidence: 80%
“…Some studies have shown that demographic and socio-economic factors such as age, gender, race, level of education and income are associated with hypertension in PLHIV [ 30 ]. For example a study in Ethiopia found that HIV diagnosed patients with some education and an average monthly income were significantly more likely to develop hypertension [ 31 ]. However, we found that while the hazard of hypertension was 0.22 and 0.59 times higher among male adults with HIV, these results were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Active smoking among our participants was seen in only 1.8%, with similar rates from studies in different parts of Ethiopia, Nigeria and Malawi. 7 , 15 , 26–29 The low prevalence of smoking in general Ethiopian population of 3.21%, the lower smoking habit of females in the country and inclusion of more females in this study can justify why only a handful of current smokers participated. 30 A study from Malawi reported that very low number of participants consumed the WHO recommended amount of fruits and vegetables similar to our study possibly resulting from resource limitation.…”
Section: Discussionmentioning
confidence: 93%
“… 31–34 There is also a wide range of findings in previous studies in Ethiopia from 12.7% to 34.3%. 5 , 15 , 16 , 26–28 , 35 Advancing age seems to be a risk for developing hypertension. 5 , 26 , 28 , 31–33 Although not consistent in all studies, males and obese individuals tend to have hypertension more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation